Study on the effect and mechanism of ultrasonic-assisted enzymolysis on antioxidant peptide activity in walnuts - Jiaying Huo; Zhaowei Cui; Ruru Zhang; Hui Ouyang; Xiaolong Liu; Ping Wang; Xiongwei Yu; Tingting Xie; Sihai Gao; Shugang Li (Ultrasonics Sonochemistry)
Walnut meal is a large quantity and high-quality resource with great exploitation value. Ultrasonic-assisted enzymolysis (UAE) was utilized in the preparation of peptides from walnut meal protein. Results indicated that by optimizing the UAE process with neutral protease, an ultrasound power of 180 W, a 4.3 h duration and an enzyme dosage of 10 KU/g, the walnut peptides exhibited the most potent antioxidant activity. In comparison to the control group, the WPI treated with ultrasound and neutral enzymes in combination (UNWPI) demonstrated a significant enhancement in their DPPH, ABTS, and ·OH scavenging capabilities, with increases of 234.23 %, 240.22 %, and 69.52 %, respectively. By analyzing the structure of walnut antioxidant peptides with or without ultrasound, it was observed that the underlying mechanism for the increased antioxidant activity was that UAE not only formed more small peptides, but also produced more peptides with hydrophobic amino acids at their terminal ends. Subsequently, six peptides were identified and screened from UNWPI, namely IFW, IIPF, IVAF, IIFY, ILAFF, and IFIP, which exhibited high antioxidant activity and could bind to Keap1 protein through hydrogen bonding, π-alkyl interactions, and π-π stacking interactions. The research results provided theoretical basis and technical support for the preparation of walnut antioxidant peptides and the high-value utilization of walnut meal.